Freeing the elephant-eating boa theorizing children in Philippine Social Science Research - Sayuno, Cheeno Marlo M. (2018)
Access online through this link: https://www.plarideljournal.org/article/freeing-the-elephant-eating-boa-theorizing-children-in-philippine-social-science-research
Keywords: Children's literature; Social science research; Literary criticism